O dialeto falado por moradores do Paraná do Jurupary- Puku/ Alenquer - PA: um estudo de variação e mudança linguística a partir da linguística histórica - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This work discusses the linguistic and cultural peculiarities of the residents of Paraná do Jurupary – Puku/Salvação Community. It is guided by the assumptions of historical linguistics based on participant intervention, bibliographical review and field research, in observations carried out in loco in the Community. The general objective of this research is to understand the historicity and contextualization that involves the native speech of the local inhabitants. Thus, the specific objectives of this research are: to discover the complexity and external variants related to the way the residents speak; to understand the language, its expressions and the main factors that contributed to the origin of the traditional speech of the community and to identify which were the linguistic influences that contributed to the formation of the native dialect, where the historical/linguistic context of the emergence of the peculiar language was investigated, through focus group interviews with the local residents, culminating in the elaboration of the research results. Data generation was carried out under the natural conditions in which the phenomena occurred, where they were observed (03 native people over 60 years of age, 03 residents between 40 and 50 years of age and 03 residents between 18 and 30 years of age). The technique used was direct observation, where, as an observer follows the daily experiences of those observed, he can try to understand their worldview, the meaning attributed to the reality that surrounds them and their own actions, as well as discover new aspects of a problem. The theoretical framework is based on the main authors: Faraco (2005), Freire (2003/ 2011), Lucchesi (2009/ 2012), Rodrigues (2018), Silva (2008). The final analysis of this research encompasses the context involving the historical/cultural and linguistic contextualization of the community, within the vast historicity of the Portuguese language, where it is recognized and highlighted that communication between local residents and their expressions used in the past are falling into disuse, due to linguistic changes that have occurred over time, new agents, external linguistic contacts, through technological evolution and new forms of communication. Thus, this linguistic peculiarity has become restricted to the oldest inhabitants, descendants of the first Portuguese immigrants from Paraná do Jurupary – Puku.
Keywords: Linguística histórica; Língua portuguesa; Jurupary-Puku; Dialeto; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE; Línguas, culturas e identidades na Amazônia